Expression of the J chain gene during B cell differentiation is inversely correlated with DNA methylation. - Yagi, M (1981)
During B cell differentiation, transcription of the J chain gene is initiated. To determine the regulatory mechanism involved, we have analyzed the structure of the J chain gene in cell lines representing successive stages in B cell development. Comparison of restriction sites showed that the J chain gene does not require a rearrangement of DNA for expression; cleavage sites present in embryonic J chain DNA were preserved through all the subsequent differentiative steps. However, comparison of 5-methylcytosine contents showed that J chain gene expression correlates with a loss of methyl groups. The J chain gene was heavily methylated in cell types not expressing J chain (i.e., embryo and lymphomas representative of immature and mature B cells) and significantly less methylated in cell lines representative of antigen-stimulated lymphocytes synthesizing J chain. These changes in J chain gene methylation represent a specific differentiation-induced response. Analyses of the heavy chain C mu and C gamma 2b genes, which are expressed at earlier and later stages than the J chain gene, showed that the C mu sequences were undermethylated in all cell types examined whereas the C gamma 2b sequences were undermethylated only in cell lines expressing the IgG2b protein. The primary encounter of a B cell with antigen must therefore trigger events that effect J chain gene transcription through a mechanism involving loss of methyl groups from cytosine.